Engagement through Emancipation, Empowerment, and Equity: Heutagogy and the 21st-Century Classroom - Perchard, Stephen R. (Scholarship@Western, 2022)
Low student engagement has become a problem for Engagement Academy (a pseudonym), as well as for most schools in Newfoundland and Labrador. Data indicates that approximately 70% of graduating students are disengaged and feel their educational experience is not adequately preparing them for life in the 21st-century. Issues related to student engagement reflect the failure of the province’s school system to adapt to societal trends and remain relevant in the 21st-century. Although a 21st-century workforce values competencies such as creativity, critical-thinking, and collaboration, traditional school systems value and reward compliance and conformity. Worse, a critical examination of traditional education systems reveals that many school structures preserve and perpetuate systemic inequities that harm its most marginalized students. This organizational improvement plan employs a humanistic lens that draws upon instructional, transformational, servant, and distributed leadership models that emancipate students from the oppressive structures of traditional schools. The implementation of classroom practices based on heutagogy and the adoption of the pedagogy-andragogy-heutagogy continuum is presented as a strategy to engage Grade 7–9 students in a 21st-century educational environment. Kotter’s eight-step model for organizational change and cycles of collaborative inquiry guides teachers through the change process. The concerns-based adoption model provides a framework for developing the change vision, identifying resistance factors, and monitoring change implementation. Klein’s communication model and Lewis’s stakeholder communication help to create a communication plan for the OIP.